Analysis of Cashless Payment Adoption using the Unified Theory of Acceptance and Use of Technology (UTAUT) - Dinda, Rahma; Alfarisy, Mohamad Fany; Rahim, Rida (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the adoption of cashless payments in West Sumatra using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The variables studied include Perceived Usefulness, Perceived Ease of Use, Social Influence, Facilitating Conditions, and Lifestyle Compatibility on the Intention to Use and Adoption of Cashless Payments, moderated by gender and level of education. The method used in this research is Structural Equation Modeling (SEM) with SmartPLS 4.0. Data was obtained from questionnaires distributed to 210 respondents in the cities of Padang, Pariaman, Padang Panjang, Bukittinggi, Payakumbuh, and Solok. The results showed that facilitating conditions and compatibility had a significant positive effect on the intention to use cashless payments, while perceived usefulness, ease of use, and social influence had no effect on the intention to use cashless payments. Furthermore, the intention to use cashless payments had a significant positive effect on the adoption of cashless payments. Meanwhile, gender and education level did not have a significant effect on the relationship between the independent variables and the intention to use cashless payments. This study implies that the government needs to improve facilities and technological support for cashless payment users. It also suggests that researchers should consider other variables that may affect the use of cashless payments in future studies.